SOSIALISASI KONSEP QUINTUPLE HELIX DALAM MEWUJUDKAN DESA KREATIF DI DESA KEDUNGDALEM KABUPATEN PROBOLINGGO - Marwiyah, Siti; Mudhofar, Muhammad; Winarto, Bambang; Queen, Mareta Syamsya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Creative villages are currently in the spotlight of the local government as an effort to increase village resources that can develop superior innovations from the creative economy subsector. Creative villages have a close relationship with the quintuple helix concept, which in its implementation involves government, academics, economic actors, society and the environment to build creative village synergy. The aim of this service is to provide understanding and provide solutions as an effort to create a developing and creative village. As in Kedungdalem Village, Probolinggo Regency, creating a creative village requires the involvement of various parties and key actors for empowerment. The initial implementation of this service was outreach to the Kedungdalem village community. This community service is carried out using the method of socialization and education to the community by providing counseling. With the existence of a service program regarding the quintuple helix concept, it is hoped that it can create a creative village in Kedungdalem village, especially in implementing the implementation of government policies in creating village innovation. This requires the cooperation of various partners in creating a strong and innovative creative village. Keywords: Creative village, quintuple helix, socialization